Comparison between red wine and isolated trans-resveratrol in the prevention and regression of atherosclerosis in LDLr (-/-) mice - Chassot, Lívia Nedel (2018)
Moderate consumption of red wine has been widely associated with reduced cardiovascular risk, mainly due to its composition in phenolic compounds with antioxidant activity, such as trans-resveratrol. Our aim was to compare the effect of red wine vs trans-resveratrol consumption on the prevention and regression of atherosclerosis in LDLr (-/-) mice. This study consisted of two protocols: \"PREVENTION\" (PREV) and \"REGRESSION\" (REGR). Both protocols included four groups: red wine (WINE), dealcoholized red wine (EXT), trans-resveratrol (RESV), and control (CONT). In PREV protocol, animals received a normal diet for 8 weeks and then switched to an atherogenic diet for the following 8 weeks, while the opposite was performed during REGR protocol. Animals that received atherogenic diet after an initial period on a normal diet (PREV) gained more body weight (39.25 ± 2.30%) than the opposite (29.27 ± 1.91%, p=0.0013), suggesting an interaction between age and weight gain. Trans-resveratrol showed the highest hypocholesterolemic effect in PREV protocol, reducing total cholesterol, LDL-C and VLDL-C, but also HDL-C. The supplementation with trans-resveratrol and dealcoholized red wine changed the fatty acids profile in the liver in both protocols, leading to an increase of MDA concentrations and SOD activity in PREV protocol. All three forms of supplementation altered biomarkers of oxidative stress and lipidemia but presented no effect on the prevention or regression of fatty streaks. These results suggest that the cardiovascular protection associated with the \"French Paradox\" may be a result of synergistic effects between wine and the Mediterranean diet.